ANALISIS PENERAPAN KEWAJIBAN PPH PASAL 23 PADA KOPERASI SUMBER KARYA DI WONOGIRI - Ita Juniarti Saputri, Fadjar Harimurti & Suharno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this research is to analyze income tax article 23 in calculation of deposit and reporting on Koperasi Sumber Karya. Another purpose of this research is to analyze tax compliance in Indonesia especially income tax article 23 because there is use withholding tax. This research use descriptive method to analyze application income tax article on Koperasi Sumber Karya. The data used document calculation of deposit and reporting in 2017. That results of the research are that taxpayers Koperasi Sumber Karya has performed the calculation of depositing and reporting well and true for income related to the use of property but not doing the use of services, Koperasi Sumber Karya not doing the calculation of depositing and reporting.Keywords: income tax article 23, calculation, depositing, reporting.